2015
DOI: 10.1016/j.ijrobp.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

A Radiation-Induced Hippocampal Vascular Injury Surrogate Marker Predicts Late Neurocognitive Dysfunction

Abstract: Purpose We aimed to develop a hippocampal vascular injury surrogate marker for early prediction of late neurocognitive dysfunction in patients receiving brain radiotherapy (RT). Methods and Materials 27 patients (17 males and 10 females, age 31–80 years) were enrolled in an IRB-approved prospective longitudinal study. Patients were diagnosed with a low-grade glioma or benign tumor and treated by 3-D conformal or intensity-modulated RT with a median dose of 54 Gy (50.4–59.4 Gy in 1.8-Gy fractions). Six dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 37 publications
3
27
1
Order By: Relevance
“…After controlling dose and pathology (glioma vs non-glioma), age showed an interaction effect with dose, as AD/RD changed greater in elderly than in younger patients when received the same dose. Female patients had larger reductions in AD/RD than males given the same dose, consistent with previous observations (25-27) where sex-dependent differences in hippocampal plasticity as well as sex hormone (26) were reported as contributing factors to higher mortality and morbidity in females due to radiation-induced injury (27). Patients with glioma had a larger reduction in AD/RD than those without, possibly due to compromise of normal appearing WM by infiltrating glioma cells.…”
Section: Resultssupporting
confidence: 91%
“…After controlling dose and pathology (glioma vs non-glioma), age showed an interaction effect with dose, as AD/RD changed greater in elderly than in younger patients when received the same dose. Female patients had larger reductions in AD/RD than males given the same dose, consistent with previous observations (25-27) where sex-dependent differences in hippocampal plasticity as well as sex hormone (26) were reported as contributing factors to higher mortality and morbidity in females due to radiation-induced injury (27). Patients with glioma had a larger reduction in AD/RD than those without, possibly due to compromise of normal appearing WM by infiltrating glioma cells.…”
Section: Resultssupporting
confidence: 91%
“…Another recent study of predictors for late neurocognitive dysfunction showed correlations of vascular dose-response in the left hippocampus in females with changes in memory function after radiotherapy 9 . Is it possible that only unilateral hippocampal radio-injury is responsible for subsequent neurocognitive decline?…”
Section: Discussionmentioning
confidence: 99%
“…Further, some reports suggest different post radiotherapy and/or post surgery changes in the two hippocampi. As a result, unilateral hippocampal sparing has been proposed [7][8][9][10][11] . The most important neurocognitive domain affected by WBRT is memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging-related biomarker identification for normal tissue injury and response in patients receiving radiation is one area of investigation that may show potential promise in identifying patients in whom prevention and interventional strategies are needed. MRI-based vascular hippocampal marker parameters related to blood-brain barrier permeability, K(trans), and the fraction of blood plasma volume, Vp, have recently been evaluated as markers of injury 34 , correlating significantly with changes in memory function at 6 and 18 months after treatment, suggesting that K(trans) could serve as one predictor of late neurocognitive dysfunction for patients.…”
Section: Imaging Cns Radiation Effectsmentioning
confidence: 99%